The Effectiveness of the MIUTV Islamic Podcast Channel on the Religious Understanding of Students of the Islamic Religious Education Study Program at UIN Madura - Muhammad Sobran Jamil Imamuddin; Muliatul Maghfiroh (al-Afkar, Journal For Islamic Studies, 2026)
The development of information technology has changed the way people, especially students, access and study religious knowledge. The channel podcast Islami MIUTV serves as a learning and dakwah medium offering easily accessible and flexible religious content. This study aims to examine the effectiveness of using the channel podcast Islami MIUTV in improving pemahaman keagamaan among students of the Program Studi Pendidikan Agama Islam (PAI) UIN Madura.The method used is deskriptif kuantitatif with data collection through an online questionnaire containing statements about podcast effectiveness and the level of students’ pemahaman keagamaan. A total of 100 students participated as respondents in this study. Data analysis involved validity, reliability, normality tests, and Product Moment correlation test using IBM SPSS software.The results showed a positive and significant correlation between the effectiveness of the channel podcast Islami MIUTV and students’ pemahaman keagamaan, with a correlation coefficient value of 0.823 and significance value of 0.000. The coefficient of determination (R²) of 0.678 indicates that 67.8% of the variance in pemahaman keagamaan can be explained by the use of this podcast. The t-test showed a significant t-value (9.733 > 2.014).